2020
DOI: 10.1002/jssc.201901103
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of volatile organic compounds in indoor environments using thermal desorption with comprehensive two‐dimensional gas chromatography and high‐resolution time‐of‐flight mass spectrometry

Abstract: Building-related health effects are frequently observed. Several factors have been listed as possible causes including temperature, humidity, light conditions, presence of particulate matter, and microorganisms or volatile organic compounds. To be able to link exposure to specific volatile organic compounds to building-related health effects, powerful and comprehensive analytical methods are required. For this purpose, we developed an active air sampling method that utilizes dual-bed tubes loaded with TENAX-TA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…These results are in line with results obtained from a non‐targeted indoor VOCs study using GC × GC coupled to a high‐resolution mass spectrometer [36]. The authors reported an average agreement of within 8 RI units and an SD of ±23 RI units [36]. Compounds that were closely associated with the wrist included 6‐methyl‐1‐heptanol, 3‐(4‐isopropylphenyl)‐2‐methylpropionaldehyde, 2‐phenoxyethyl isobutyrate, and 2,4,6‐trimethyl‐pyridine.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…These results are in line with results obtained from a non‐targeted indoor VOCs study using GC × GC coupled to a high‐resolution mass spectrometer [36]. The authors reported an average agreement of within 8 RI units and an SD of ±23 RI units [36]. Compounds that were closely associated with the wrist included 6‐methyl‐1‐heptanol, 3‐(4‐isopropylphenyl)‐2‐methylpropionaldehyde, 2‐phenoxyethyl isobutyrate, and 2,4,6‐trimethyl‐pyridine.…”
Section: Resultssupporting
confidence: 89%
“…On average the agreement between experimental and database LRIs was ±2 RI units (SD ±8 RI units). These results are in line with results obtained from a non-targeted indoor VOCs study using GC × GC coupled to a high-resolution mass spectrometer [36]. The authors reported an average agreement of within 8 RI units and an SD of ±23 RI units [36].…”
Section: Comparison Of Ankle and Wrist Skin Chemical Profilessupporting
confidence: 87%
See 2 more Smart Citations
“…However, there is still not an air quality strict regulation and their presence in urban air is mostly produced by common anthropogenic sources like intense traffic emissions, and recent studies have demonstrated that car tires wear contribute to release PAHs and other compounds to the ambient air [8][9][10]. Different procedures, based on passive [11,12] as well as active [13][14][15] air sampling, have been proposed for the extraction of different organic pollutants, including PAHs, polychlorinated biphenyls, plasticizers, or flame retardants in air. In most cases, the analytes are trapped onto an appropriate sorbent such as polyurethane foam, XADresin, or carbon-based materials as well as mixtures of different sorbents, followed by thermic or solvent desorption [15][16][17].…”
Section: Introductionmentioning
confidence: 99%